Sustainability of Singapore’s transportation system. - Huang, Guanhua. (2008)
Singapore is an island city-state of 685 square km in area. Currently, roads constitute 12% of total land area while 15% of land area is devoted to housing. With limited land resource, we face restrictions on road capacity expansion. The number of vehicular trips grew by about 3 times from 2.7 million trips in 1981 to about 7.8 million trips in 2005. Given expected increase in population, annual vehicle growth rate of 1.5%, rising levels of income, changes in lifestyle and other demographic and social development, this number is expected to grow to more than 10 million daily trips in 10 years time. With a well developed transportation system, the challenge we face today is achieving sustainability in the long run. This paper seeks to investigate the issue of transport sustainability from threeindicators; cost, speed and environment.